2022
DOI: 10.1186/s12933-022-01554-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of remnant cholesterol beyond low-density lipoprotein cholesterol in diabetes mellitus

Abstract: Background Previous research has linked elevated low-density lipoprotein cholesterol (LDL-C) and remnant cholesterol (RC) with diabetes mellitus (DM). The present study aims to estimate the RC-related DM risk beyond LDL-C, and to investigate the extent to which the association of RC and DM is mediated via insulin resistance and inflammation. Methods We enrolled 7308 individuals without previous history of DM into the present study from the China He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 57 publications
1
38
0
1
Order By: Relevance
“…RCis gaining attention because of its close association with cardiovascular diseases [ 15 ]. Epidemiological studies have found that RC is also associated with hypertension [ 16 ], diabetes mellitus and its complications [ 17 , 18 ], nonalcoholic fatty liver disease [ 19 ], and chronic kidney disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…RCis gaining attention because of its close association with cardiovascular diseases [ 15 ]. Epidemiological studies have found that RC is also associated with hypertension [ 16 ], diabetes mellitus and its complications [ 17 , 18 ], nonalcoholic fatty liver disease [ 19 ], and chronic kidney disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The urine total arsenic concentration showed a slight upward trend in the last three survey cycles. The substance concentration below the detection limit was replaced by the lower limit of detection (LLOD) divided by square root of 2 (LLOD/SQRT [ 2 ]). The lowest median (interquartile range (IQR)) of concentrations of total urine arsenic was 6.6 (3.42–13.47) μg/L from the survey cycle 2013 to 2014, and the detection limit was 0.26 μg/L ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the spectrum of lipoproteins, there is no doubt that total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) concentrations are critically important affecting factors for the risk of cardiovascular diseases including Alzheimer’s disease (AD) [ 1 ], diabetes [ 2 ], or hypertension or Parkinson disease (PD) [ 3 ]. Cholesterol homeostasis is vital for proper cellular and systemic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological studies found that elevated RC along with a higher prevalence of DM, as such RC may be a predictor of diabetes or prediabetes and hypertension [28,29]. Additionally, a study of a population of 7308 individuals recruited from CHNS showed that the concentration of RC was associated with DM beyond the LDL-C [30]. Besides, RC also had a substantial connection with the prediction or diagnosis of hypertension, and could be used as a blood marker for screening [31,32].…”
Section: Discussionmentioning
confidence: 96%